2‐Amino‐5‐(cyanomethylsulfanyl)‐1H‐pyrroles from Propargylamines, Isothiocyanates, and Bromoacetonitrile by One‐Pot Synthetic Protocol. Issue 19 (18th May 2020) - Tarasova, Olga A.; Nedolya, Nina A.; Albanov, Alexander I.; Trofimov, Boris A.
Abstract: Tertiary propargylamines (such as N, N ‐dialkylpropargylamines, N ‐propargylpyrrolidine, ‐piperidine, and ‐morpholine), isothiocyanates, and bromoacetonitrile have been shown to be readily available building blocks for the highly selective one‐pot construction of rare‐functionalized pyrroles, namely so far inaccessible 1‐substituted 2‐amino‐5‐(cyanomethylsulfanyl)‐1 H ‐pyrroles, in up to 92 % yield. This highly efficient and operationally simple approach includes the initial formation of lithium but‐2‐ynimidothioate (adduct of monolithiated propargylamine and isothiocyanate), its transformation into potassium buta‐2, 3‐dienimidothioate under the action of the t ‐BuOK/DMSO system (through acetylene‐allene isomerization and the exchange by cations), intramolecular cyclization into potassium thienylamide (at ≤15 °C), followed by its re‐cyclization into potassium pyrrolylsulfide at a higher temperature (45–60 °C), and the final S‐alkylation of the latter with bromoacetonitrile. The total reaction time is 45–60 min. Abstract : A wide range of 1‐substituted 2‐amino‐5‐(cyanomethylsulfanyl)‐1 H ‐pyrroles have been synthesized in up to 92 % yield by the one‐pot reaction of monolithiated tertiary propargylamines with isothiocyanates, followed by sequential treatment with t ‐BuOK/DMSO and bromoacetonitrile. The process occurs through the initial formation of the thiophene core (at ≤15 °C), followed by its re‐cyclization into the pyrrole nucleus at a higher temperature (45–60 °C).